2020
DOI: 10.33403/rigeo.693769
|View full text |Cite
|
Sign up to set email alerts
|

Academic Motivation Levels of Secondary School Students and Their Attitudes Towards a Social Studies Course

Abstract: The present study aims to reveal the motivation levels of secondary school students and their attitudes towards a Social Studies course. This study employed a mixed method approach. The quantitative data were collected through the use of an "Academic Motivation Scale" and an "Attitude Scale for a Social Studies Course". The qualitative data were obtained through a structured interview. Four hundred and forty-three secondary school students participated in the quantitative part of the study, while fourty-five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A literature survey revealed that only a few studies in the field of social studies share a similar focus with the current study (Çağlar, 2022;Faiz & Karasu-Avcı, 2020;Fırat, 2019). Çağlar (2022) observed a significant relationship between middle school students' attitudes toward the social studies course and their motivation in this course.…”
Section: Conclusion and Discussionmentioning
confidence: 54%
“…A literature survey revealed that only a few studies in the field of social studies share a similar focus with the current study (Çağlar, 2022;Faiz & Karasu-Avcı, 2020;Fırat, 2019). Çağlar (2022) observed a significant relationship between middle school students' attitudes toward the social studies course and their motivation in this course.…”
Section: Conclusion and Discussionmentioning
confidence: 54%
“…1) Students' attitudes in learning different areas under social studies are the first factor that explains 8.281 percent of the variance. In their 2020 study, Melike Faiz and colleagues found that students have an increased motivation and attitude towards social studies instruction when it connects to the "study of history, having an interest in the course, and the way the course is taught" (Faiz, 2020). These are all indications that students' attitudes to learning history give them the tools to analyze and explain problems in the past.…”
Section: Extracted Factors Characterize Students' Attitude 721 Toward...mentioning
confidence: 99%
“…Attitudes cannot be observed directly but must be inferred and assessed from observable responses or behavior (see Proctor & Capaldi, 2012; Salma et al, 2020; Somblingo & Alieto, 2020). To elicit observable responses, researchers can use direct methods and presentation of stimuli such as questionnaires and interviews aimed at revealing individuals’ reactions toward particular objects (Faiz & Karasu Avcı, 2020; Gupta & Moradi, 2015; Nukapangu, 2020). The present article links sociolinguistics and social psychology, combining the study of CS and attitude to enable further insights about the intricate relationship between attitudes and behavior.…”
Section: Literature Reviewmentioning
confidence: 99%